Ser e sentir-se docente: representações das dimensões emocionais do trabalho docente em periódicos educacionais e romances memorialísticos de professoras primárias (1950 - 1970) - Costa, Marina Mendes da [UNIFESP] (2016)
Using as an approach the analysis of Cultural History, the dissertation presented here aimed to identify as representations, understood in the sense of Chartier, about the emotional dimensions of the work of primary teachers in São Paulo, between the 1950s and 1970s. For that, autobiographical novels of primary teachers who were working at that time, the magazines produced by the Centro de Professorado Paulista ? CPP, as well as the productions of the magazine Revista Nacional de Estudos Pedagógicos ? RBEP, from the Instituto Nacional de Estudos Pedagógicos were used, as a way of comparing the representations on the emotional dimensions of the teaching staff work produced by the teachers (retired professionals, teachers who were currently working, and the ones who propose themselves to represent the class) and the representations produced by the researches in education, publicized by the RBEP. The emotions are defined as a dynamic system that provides: dealing with the unknown, awareness, constant judgment, unconsciously or consciously, of the threats and opportunities of the everyday. Emotions are defined from Estrela and Damasio, as a dynamic system that provides: the dealing with the unknown, taken of conscience, constant, unconscious and conscious judgment of the threats and opportunities of daily life. The emotional dimensions of teaching work are understood as a set of emotions resulting from the interactions of teachers in the exercise of teaching: the relationship with students, family, other professionals in the school environment, as well as the emotions arising from working conditions and changes In the educational structure. The period chosen for the investigation is justified because it was a time of important actions engendered by international organizations such as UNESCO ? United Nations Educational, Scientific and Cultural Organization and OAS ? Organization of American States, that encouraged the expansion of the research in education through the creation of Regional Centers of Educational Researches, as a form to guarantee an increase in the indexes of literacy and enrollment in the country. This process contributed for the configuration of the educational field to gain a scientific character, altering the representations on the work of primary teachers. In São Paulo these representations on the work of the primary teacher also reported in the representations elaborated by CPP, in a context of intense mobilizations related to salary campaigns. The study also provided the identification, among other factors, the disappearance of the emotions in the discourse on the profession with the advance of the scientific conceptions, markedly the psychology, to the extent that the representations on the emotional dimensions of the primary teachers had more or less legitimacy according to the position of the field.